Effect of Proline Analogues on Activity of Human Prolyl Hydroxylase and the Regulation of HIF Signal Transduction Pathway - Ma, Xiaoyan; Wang, Xiaoxin; Cao, Jing; Geng, Zhirong; Wang, Zhilin (PLOS ONE, 2014)
Hypoxia inducible factor 1 (HIF-1) plays a pivotal role in cellular responses to hypoxia. Prolyl hydroxylase 3 (PHD3) degrades HIF-1α under normoxic conditions through the hydroxylation of HIF-1α for proteolysis. Inhibiting PHD3 activity is crucial for up-regulating HIF-1α, thereby acting as a potential target for treating hypoxia-related diseases. In this study, two proline analogues (PA1 and PA2) were screened as PHD3 inhibitors with apparent EC50 values of 1.53 and 3.17 µM respectively, indicating good inhibition potency. Nine proteins, significantly regulated by PA1, were identified using 2-DE coupled with MALDI-TOF/TOF MS. Pyruvate kinase isozymes M1/M2 (PKM) and alpha-enolase 1 (ENO1), which are key modulators of glycolysis, are directly regulated by HIF-1α. Moreover, VEGF, a signal protein stimulating angiogenesis, was strongly promoted by PA1. Our findings suggest that PA1 stabilized HIF-1α as well as up-regulated glycolysis and angiogenesis proteins. Herein, for the first time, we systematically studied proline analogue PA1 as a PHD3 inhibitor, which provides innovative evidence for the treatment of HIF-related diseases.